An Indicator for Sustainable Development in Indonesia: Genuine Net Saving - Yuniarti, Putri Irma (P2E-LIPI, 2013)
It has been learned that there are conflicting approaches between economic development and environmental preservation. It happens because economic development focuses on how to achieve the goals of development, often by exploiting natural resources, which can lead to environmental degradation. Information around the depletion of natural resources and environmental degradation has not been included within Indonesian economic indicators yet. Apparently, Indonesia has a high rate of economic growth, shown by the increasing amount of national income. Yet, this result can come up with the exclusion of the environmental costs. In fact, environmental exploitation and natural resources extraction, results of excessive economic growth, later on will eventually cause problems and might even hamper economic development. This paper investigates these issues because they are related to one of the indicators of sustainable development, that is, Genuine Net Saving, which is the indicator of whether economic development in Indonesia meets the terms of a weak sustainability criterion. Calculating genuine net saving is carried out by reducing Indonesiaâs national saving as a cost of capital from depreciation, depletion of natural resources, and the cost of environmental degradation. The results indicate that development in Indonesia does not meet the criteria of weak sustainability, which means that it is not environmentally sustainable.